2007
DOI: 10.1177/0363546507301585
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Neuromuscular Control of the Trunk Predict Knee Injury Risk

Abstract: Factors related to core stability predicted risk of athletic knee, ligament, and ACL injuries with high sensitivity and moderate specificity in female, but not male, athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
595
1
29

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 731 publications
(636 citation statements)
references
References 39 publications
11
595
1
29
Order By: Relevance
“…The core stability is defined as the ability to control the stem in response to the internal and external disturbances, and studies indicate that increased trunk stability decreases the risk of knee injuries, especially in women 23,24 . The return to sports training allows the patient to gradually experience the game situations, increasing thus the functional ability and confidence of the athlete.…”
Section: Discussionmentioning
confidence: 99%
“…The core stability is defined as the ability to control the stem in response to the internal and external disturbances, and studies indicate that increased trunk stability decreases the risk of knee injuries, especially in women 23,24 . The return to sports training allows the patient to gradually experience the game situations, increasing thus the functional ability and confidence of the athlete.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the hip joint is the cause of dysfunction or the victim, there has been evidence since 1939 that there exists a chain of adaptive reactions changing movement patterns throughout the system. This can occur from the foot up to the pelvis and from the trunk down to the foot [53][54][55][56][57][58][59]. Bullock-Saxton [60] and Janda [40] demonstrated this further in examining muscle activation patterns in male athletes who had chronic ankle sprains (> four months).…”
Section: Layer Iv: Neuro-mechanical Layermentioning
confidence: 96%
“…Recent reports have shown that decreased neuromuscular control and high-risk biomechanics of movement are predictors of injury and re-injury [74][75][76]. Improved understanding of these biomechanical, anatomic, and kinematic risk factors of ACL injuries has led to the development of ACL injury prevention programs.…”
Section: Risk Factors and Preventionmentioning
confidence: 99%